The relationship of knowledge management and market segmentation on CRM - Mohammadhossein, Nastaran (2013)
The move in recent times towards customer-centric business shifts companies and organizations to be more cautious about customers and clients. Customer relationship management (CRM) has become one of the recognized business strategies in order to manage business dealings with customers. This requires companies to recognize the importance of managing the customer’s knowledge, and subsequently categorizing and segmenting this knowledge to provide the best product and service for the customers. This will then result in successful CRM implementation. The objective of this study is to conceptualize and validate the concept of Knowledge Management and Market segmentation in CRM effectiveness by proposing a model. Based on a survey of 150 customers of a company in Malaysia using the CRM system, the study results demonstrate a large, significant, positive relationship between Knowledge Management (KM) Competence and Market segmentation (MS) dimensions with CRM dimensions. Hypotheses are examined through Partial Least Squares (PLS) procedure and the software programs which have been used for analyzing the data is SmartPLS. The results of the model showed that there is a positive relationship between CRM and two proposed hypotheses, namely: MS and KM. Hence, attention and the investing of significant effort on market segmentation and knowledge management in the companies and the organizations would be efficient in the success of CRM. The instrument and comprehensive model in this paper would be valuable and beneficial both for future researchers and practitioners interested in developing CRM effectives.